Peoples' Democratic Party and selection of gubernatorial candidate in North-West Nigeria - Yusuf, Yahaya Musa (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2017)
Political parties provide the platforms on which candidates contest elections in a multiparty democracy. Many methods exist for the selection process by political parties. In some places, it is regulated by legal framework and in others; there is a greater level of flexibility. Many factors affect this process particularly in emerging democracies that grapple with primordial political culture. The Peoples' Democratic Party (PDP) has been in power since the return of democracy in 1999. However, it suffered a heavy defeat at all levels. It is argued that what led to this failure was how the party conducted its candidate selection. This study attempts to study how the PDP selects its governorship candidates at the state level in North-West Nigerian States. This is in order to assess the factors that affect the selection process. The study employs mixed method both in data collection and analysis. For data collection, the research uses a questionnaire and in-depth interviews to collect data from the delegates and party executives who participated in the selection for the period under study. A sample size of 450 is used out of the 2646 research population. Also, 15 party executives were also selected for the interviews. A 5-point Likert scale is used in the questionnaire while 10 structured questions were administered for the face to face interview. Statistical Package for Social Science (SPSS) tool is used to analyse the quantitative data collected while thematic and documentary methods of analyses were also used in the analysis of the in-depth interviews conducted. The findings of this research show that Party executive significantly influences gubernatorial candidates' selection in North-Western geopolitical zone of Nigeria. Serving PDP governors use their incumbency power to influence gubernatorial candidates' selection in their favour. Factions within the party make significant impact in gubernatorial candidates' selection. More so, Party benefactors are very much relevant in the party gubernatorial candidates' selection. Ethno-religious sentiment is a factor in the party's gubernatorial candidates' selection. Party benefactors and ethno-religious sentiments inflict faction among party members in the party gubernatorial candidates' selection. Party members' factions affect quality gubernatorial of candidates' selection within political party. The 2011 PDP gubernatorial primary election is better in quality than that of 2014. This means that there is strong relationship between gubernatorial candidates' selection and electoral success because the party failed in 2015 election due to the lack of credibility in the 2014 gubernatorial candidate selection. Therefore, this has led to the conclusion that despite observance of rules, internal party politics is full of problems which led to party members' defection, factionalism, and loosing elections in the PDP North-Western geopolitical zone.